Islam At the Crossroads of Global Ethics: An Ecumenical-Pluralist Reading of Hans Küng (1928-2021) - Tijani Boulaouali (Al-Jami'ah: Journal of Islamic Studies, 2025)
Religious and cultural pluralism has introduced a new approach that differs from classical European orientalism, taking into account the historical, socio-cultural, and political transformations experienced by Western societies in their shift from monoculturalism to pluralism. Contemporary Western scholars, philosophers, and theologians have given significant space to Islamic components, offering pluralism as one of the most objective frameworks for interacting with Islam. Hans Küng stands out among other thinkers for his objectivity, courage, and ability to deconstruct Orientalist assumptions that approach Islam from a narrow ideological perspective. This study explores Küng’s main ideas and projects, particularly his concepts of global ethics, pluralism, interfaith dialogue, competing paradigms, and the reinterpretation of the friend-enemy dichotomy. This study shows that Küng’s theological and philosophical foundation in interacting with Islam is closely related to his personal experiences and intellectuality. This led him to initiate a global ethics project as a moral foundation for interfaith dialogue. Küng positions Islam in the context of cosmic pluralism as an important component in the equation of international peace and interfaith dialogue, not only through its tolerant teachings, but also through its rich legal and philosophical heritage, which has contributed to the advancement of human civilization. Therefore, he calls for a reinterpretation of Islam and a deconstruction of contemporary Muslim challenges through competing paradigms to find a viable way out of the current crisis of civilization.[Pluralisme agama dan budaya telah memperkenalkan pendekatan baru yang berbeda dari pembacaan orientalistik Eropa klasik, dengan mempertimbangkan transformasi historis, sosio-budaya, dan politik yang dialami oleh masyarakat Barat dalam pergeseran mereka dari monokulturalisme ke pluralisme. Cendekiawan, filsuf, dan teolog Barat kontemporer telah memberikan tempat yang signifikan bagi komponen Islam, dengan menawarkan pluralisme sebagai salah satu kerangka kerja paling objektif untuk berinteraksi dengan Islam. Hans Küng menonjol di antara para pemikir lainnya karena objektivitasnya, keberaniannya, dan kemampuannya untuk mendekonstruksi asumsi-asumsi orientalistik yang mendekati Islam dari perspektif ideologis yang sempit. Studi ini mengeksplorasi gagasan dan proyek utama Küng, terutama konsepnya tentang etika global, pluralisme, dialog antaragama, paradigma yang bersaing, dan reinterpretasi dikotomi teman dan musuh. Studi ini menunjukkan bahwa landasan teologis dan filosofis Küng dalam berinteraksi dengan Islam sangat berkaitan erat dengan pengalaman pribadi dan intelektualitasnya. Hal tersebut membawanya untuk menggagas proyek etika global sebagai landasan moral untuk dialog antaragama. Küng memposisikan Islam dalam konteks pluralisme kosmis sebagai komponen penting dalam persamaan perdamaian internasional dan dialog antaragama, tidak hanya melalui ajaran-ajarannya yang toleran, tetapi juga melalui warisan yuridis dan filosofisnya yang kaya, yang telah berkontribusi pada kemajuan peradaban manusia. Oleh karena itu, ia menyerukan reinterpretasi Islam dan dekonstruksi tantangan Muslim kontemporer melalui metodologi paradigma yang bersaing untuk menemukan jalan keluar yang layak dari krisis peradaban saat ini.]